Formação profissional de formadores de professores de matemática : contextos e práticas pedagógicas na licenciatura em Parintins - Beltrão, Isabel do Socorro Lobato (2018)
ABSTRACT: The object of this study is the professional preparation of the teacher trainer and the knowledgebuilding processes in their pedagogical practices, which aims to understand the experiences of teachers' educators, referring to their experience in the process of construction of knowledge, underlying the pedagogical practices in the undergraduate program in Mathematics in ParintinsAM. It was used the teacher trainer nomenclature to refer to the professor who works in the Mathematics undergraduate program. Based on the qualitative perspective, this research has developed into a methodological approach to Thematic Oral History. The interlocutors were eight Mathematics teachers’ trainers at the Amazonas State University (UEA), who work at the Center for Higher Studies in Parintins (CESP). In addition to the records and observations carried out during the investigative course, the analysis of documents and narrative interviews, which were recorded in audio, were also used as data-building tools. All interviews were transcribed entirely, textualized and validated by the research interlocutors. The analysis of the constructed data was carried out through the analysis of narratives, based on the Discursive Textual Analysis (ATD), because we understand that this method is open to other methodological pathways. The results of this study have made it possible to conclude that each teacher trainer experiences a singular pathway and that his/her teaching experiences are constructed and reconstructed, constantly, according to the knowledge that is resignified throughout their experiences in training and professional formation. The trainers showed that their practices and experiences produced underlying knowledge, both in the practices of teaching Mathematics, and in the pedagogical practices of training teachers. Such revelations allowed us to infer that the way in which the interlocutors experience their experiences in the Mathematics undergraduate program broaden their chances of success in training Math teachers. RESUMEN: El objeto de este estudio es la formación del docente y los procesos de construcción de conocimientos en sus prácticas pedagógicas, que pretenden comprender las experiencias de los educadores de los docentes, refiriéndose a su experiencia en el proceso de Construcción del conocimiento, subyacente a las prácticas pedagógicas en el grado en matemáticas en Parintins-AM. Se utilizó la nomenclatura formadora de formadores para referirse al profesor que trabaja en el grado de matemáticas. Basándose en la perspectiva cualitativa, la investigación se ha convertido en un enfoque metodológico de la historia oral temática. Los interlocutores fueron ocho formadores de profesores de matemáticas en la Universidad del estado de Amazonas (UEA), que trabajan en el centro de estudios superiores de Parintins (CESP). Además de los registros y observaciones llevadas a cabo durante el curso de investigación, el análisis de documentos y entrevistas narrativas, que se registraron en audio, se utilizaron como herramientas de creación de datos. Todas las entrevistas fueron transcritas enteramente, textualizadas y validadas por los interlocutores de la investigación. El análisis de los datos construidos se llevó a cabo a través del análisis de las narrativas, basándose en el análisis textual discursivo (ATD), porque entendemos que este método está abierto a otras vías metodológicas. Los resultados de este estudio han permitido concluir que cada docente es un curso singular y que sus experiencias docentes se construyen y reconstruyen, constantemente, según el conocimiento que refieren a lo largo de sus experiencias en Formación y Constitución profesional. Los formadores mostraron que sus experiencias y experiencia producían conocimientos subyacentes, tanto en las prácticas de enseñanza de matemáticas, como en las prácticas pedagógicas de formación de docentes. Dorval revelaciones nos permitieron deducir que la manera en que los interlocutores experimentan sus experiencias en el grado de las matemáticas, amplían sus ocasiones del éxito en graduar a profesores de la matemáticas.